2015
DOI: 10.1177/1742271x14567498
|View full text |Cite
|
Sign up to set email alerts
|

The ScanTrainer obstetrics and gynaecology ultrasound virtual reality training simulator: A cost model to determine the cost viability of replacing clinical training with simulation training

Abstract: The aim of this study was to produce an economic cost model comparing the use of the Medaphor ScanTrainer virtual reality training simulator for obstetrics and gynaecology ultrasound to achieve basic competence, with the traditional training method. A literature search and survey of expert opinion were used to identify resources used in training. An executable model was produced in Excel. The model showed a cost saving for a clinic using the ScanTrainer of £7114 per annum. The uncertainties of the model were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…In quality assessment of the 27 primary research articles, 21 were scored as high quality (≥75/100 points), 14–34 3 as medium quality (50-74/100 points) 35–37 and 3 were scored as low quality (<50/100 points). 38–40 The detailed QHES evaluations are provided in online supplemental file 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In quality assessment of the 27 primary research articles, 21 were scored as high quality (≥75/100 points), 14–34 3 as medium quality (50-74/100 points) 35–37 and 3 were scored as low quality (<50/100 points). 38–40 The detailed QHES evaluations are provided in online supplemental file 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 included studies, 11 were randomized trials [1,5,[15][16][17][18][19][20][21][22][23] and three were observational two group studies [24][25][26]. One study was a cost effectiveness study involving a questionnaire [27]. Participants in the included studies involved postgraduate trainees (n = 437 (69.7 %)), medical students (n = 154 (24.6 %)), and midwives/certified nurses (n = 36 (5.7 %)).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Moreover, the number of studies available for the metaanalysis was limited due to the poor quality of reporting of results in several studies. Finally, the study examining the cost-effectiveness of training on a specific ultrasound simulator [27] was initiated and sponsored by the manufacturer, which may result in some risks of bias.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials using a simulator demonstrated significant improvement in TVUS skills among 1st‐year residents as well as retention 2 months later . While cost‐effective, the cost of the simulator (approximately $32,000) may be prohibitive for many training institutions . Another study described the use of patient models to teach TVUS skills .…”
Section: Introductionmentioning
confidence: 99%